2020
DOI: 10.3390/ijerph17176303
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Game Theory Study for Construction and Demolition Waste Recycling Considering Green Development Performance under the Chinese Government’s Reward–Penalty Mechanism

Abstract: The low efficiency of the closed-loop supply chain in construction and demolition waste (CDW) recycling has restricted the green development of China’s construction industry. Additionally, the government’s reward–penalty mechanism has a huge influence on green development. This study aimed to investigate the effect of green development performance (GDP) and the government’s reward–penalty mechanism on the decision-making process of production and recycling units, as well as to reveal the optimal strategies und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 67 publications
0
49
0
Order By: Relevance
“…Research hypothesis 4: Customer as balanced scorecard perspective influences significantly bank strategic mechanism. Table (1), demonstrates observed data correlation matrix which conducted by applying factors analysis for all variables (financial, internal process, organizational capacity and customer). The findings revealed that all variables' range between 0.001 to 1.00 this indicated that all factors are sufficient to be used to measure strategic mechanism.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research hypothesis 4: Customer as balanced scorecard perspective influences significantly bank strategic mechanism. Table (1), demonstrates observed data correlation matrix which conducted by applying factors analysis for all variables (financial, internal process, organizational capacity and customer). The findings revealed that all variables' range between 0.001 to 1.00 this indicated that all factors are sufficient to be used to measure strategic mechanism.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The viewpoint of structural theory has been broadly adopted in the social sciences in order to analyze social and institutional developments as well as their causes and implications (Long et al 2020). Strategic management analysis focused on an interpretive aspect was also inspired by institutional theory (Anwar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Green development is a complex adaptive system composed of legal policy systems, production systems and living systems and is closely related to society, economy and the natural environment. The community of human and natural life is at the core of green development [ 1 , 2 ]. The green development of industrial enterprises, a major concern of industrial ecology and environmental economics researchers, regards industrial enterprises as the main body, e.g., the effect of the market mechanism on the green development of industrial enterprises [ 3 ], the effect of industrial agglomeration on green development efficiency [ 4 ], the influencing mechanism of technology R&D on green development in China’s industrial sector [ 5 ] and the evaluation framework of industrial green development [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…e greater the p value, the higher the core position of enterprise A. In addition, the government will give necessary incentives M to enterprises that actively participate in collaborative innovation, and corresponding punishment N to opportunists (i.e., passive participant), so as to guide and restrain the behavior of participants in collaborative innovation [27].…”
Section: Model Hypothesismentioning
confidence: 99%